Entrepreneurship and liminality: the case of self-storage based businesses. Issue 3 (3rd May 2016) - Daniel, Elizabeth; Ellis-Chadwick, Fiona
Abstract : Purpose: – The purpose of this paper is to apply the theoretical lens of liminality to a consideration of non-traditional entrepreneurial locations. The study exemplifies such locations by empirically exploring self-storage based businesses: that is, businesses that operate for a significant number of hours each week from self-storage facilities. Design/methodology/approach: – The study draws on interviews with entrepreneurs operating self-storage based businesses and operators of self-storage facilities. The interview data is supported by site visits, businesses' websites, promotional and marketing materials and press coverage. Findings: – Consistent with the liminal lens, entrepreneurs view their time operating from self-storage as a transitional phase. They do not suffer the high levels of uncertainty and unsettledness usually associated with liminality. However, they experience anxiety related to perceptions of operating from a business location outside the mainstream. Whilst the entrepreneurs benefit from additional services provided by the self-storage operators, this may be at the expense of extra "liminal" work and anxiety experienced by the storage operators' staff. Originality/value: – The study contributes to entrepreneurship by answering Steyaert and Katz's (2004) call for studies in unfamiliar places and spaces. The authors identify a number of ways in which liminality can arise when considering entrepreneurial locations. Drawing on extant entrepreneurial studies, the authors theorise that idiosyncratic characteristics of such spaces attract entrepreneurs with particular personal characteristics and needs, who will in turn be influenced by those spaces. In the case of self-storage facilities, the liminal space allows trepidatious entrepreneurs to "try on" (Hawkins and Edwards, 2015, p. 39) operating a new venture.